Saving Strategies of the Population: Main Notions and Operationalization - Елена Скурятина (Journal of Economic Sociology, 2010)
The paper is considering the main approaches to the explanation of saving behavior, focusing on strategic approach. Firstly the theoretical definition of “saving strategy” is given and after that this term is operationalized on the empirical level. Special attention goes for the problems and restrictions of this approach usage.